2019
DOI: 10.1002/aqc.3085
|View full text |Cite
|
Sign up to set email alerts
|

Saltmarsh conservation through inventory, biogeographic analysis and predictions of change: Case of Tasmania, south‐eastern Australia

Abstract: 1. Effective conservation of saltmarshes involves detailed and accurate mapping of their range, area of occupancy and plant community composition as part of region-wide inventories. There is also a need to identify the major mesoscale influences on the distributions of types of saltmarsh, obligate saltmarsh plants and salt pans, and evaluate possible responses to macroclimatic changes.2. Tidal saltmarshes of Tasmania and its offshore islands (coastline of 4,882 km, spanning latitudes 39°40′ to 43°40′S), off so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…2). This region contains nearly 25% of the mapped saltmarsh in Tasmania (Prahalad & Kirkpatrick 2019). Saltmarshes occupy 1,326 ha of coastal embayments, estuaries and tidal islands between Temdudheker/Woolnorth Point and Stanley (Prahalad 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This region contains nearly 25% of the mapped saltmarsh in Tasmania (Prahalad & Kirkpatrick 2019). Saltmarshes occupy 1,326 ha of coastal embayments, estuaries and tidal islands between Temdudheker/Woolnorth Point and Stanley (Prahalad 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sampling sites in Duck Bay, near Smithton in far northwest Tasmania, southeastern Australia. Coastal saltmarsh mapping data sourced from Prahalad and Kirkpatrick (2019), Spartina anglica mapping sourced from Prahalad (2016). Base data from the LIST ( www.thelist.tas.gov.au, accessed 9 March 2022; State of Tasmania).…”
Section: Methodsmentioning
confidence: 99%
“…There are ,1048 ha of saltmarshes fringing the Lagoon (Fig. 1), which is close to one-fifth of the Tasmanian extent (Prahalad and Kirkpatrick 2019). Tasmanian coastal saltmarshes, including those in Moulting Lagoon, are recognised as 'threatened ecological communities' under the Australian Federal Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act).…”
Section: Study Areamentioning
confidence: 99%
“…Tasmania has about 58.6 km 2 of coastal saltmarshes, principally located on the east coast and Flinders Island, the north coast and the far northwest including King Island (Prahalad & Kirkpatrick 2019). Although only a small proportion of the Australian total, Tasmania features the highest diversity of saltmarsh vegetation communities (Saintilan 2009a(Saintilan , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…Gouldthorpe (2000) researched the impacts of drainage and grazing on Derwent River marshes and a recent study identified changes in the extent and community composition of southeast Tasmanian saltmarshes (Prahalad et al 2011). The real and projected impacts of climate change have also received recent attention (Mount et al 2010, Prahalad et al 2015, Prahalad & Kirkpatrick 2019. Nevertheless, there are no Tasmanian studies with detailed field measurements that focus on the interactions of saltmarsh soils and vegetation.…”
Section: Introductionmentioning
confidence: 99%